STATE STIMULATION OF TRANSFORMATION OF POWER INDUSTRY - V. A. Zubakin (Стратегические решения и риск-менеджмент)
Transition to digital technologies in management of power industry at all levels – an inevitable consequence of the technical progress which has generated opportunities for diversification, decarbonization and decentralization. Thus it is necessary to recognize that digitalization in power industry is NOT automation, and first of all creation of new business models, services and the markets with a support on possibility of digital economy. In this article questions of transformation of architecture of power industry, and also the main restrictions are considered: absence in regulatory base of new opportunities for consumers; general system inefficiency; impossibility “to legalize” appearance of new subjects (active consumers and prosumers, operators of micropower supply systems and aggregators of the distributed power objects, various service organizations), and also to deregulate the relations between them, to standardize interaction interfaces with EEC, to transform the energy markets.In article it is offered for transition to new digital power to make corresponding changes to the legislation: to enter new type of participants of the market (the active consumer, an active power complex), operated intellectual connection carrying out the standard with the electrical power system, completely responsible for management of the power supply and thus having the minimum regulatory restrictions on organizational model of the work; to improve rules of functioning of trade systems for creation of the markets of the distributed power providing an effective exchange of goods and services between traditional participants of the markets and participants of new type; to enter possibility of application of technologies of the coordinated management of the distributed sources and consumers of energy, systems of storage of energy, means of regulation of loading (“aggregators”) for the purpose of increase of efficiency of their use and participation in the electric power and power markets, including rendering system services and performance of other functions in these markets (the pilot project of such system is realized under the leadership of the author of the present article by subsidiary PAO “Lukoil” “Energy and gas of Romania”); to increase technological and economic flexibility of conditions on reliability and quality of power supply, creation of possibility of a choice by the consumer of conditions of power supply necessary for him and the account them in cost; to enter the accounting of the opportunities given by “new” decisions, at an assessment, formation and implementation of investment programs of the adjustable companies (including introduction of a technique of an assessment of investment projects at possession cost on all life cycle of the decision); to replace cross subsidizing of the population by industrial consumers with mechanisms of address social support and / or with system of restriction of volumes of consumption on reduced rates (“соцнорма”); to refuse further deployment of system of subsidizing of power supply of one regions at the expense of consumers of other regions (as it leads to growth of inefficient power consumption in the subsidized regions, not provided with available generation and infrastructure); to change norms of technical regulation, norms of design on the basis of new technologies; to make changes to programs of development of the infrastructure organizations of power industry taking into account trends of diversification, decentralization, decarbonization and a digitalization; to provide possibility of stimulation, including tariff, implementation of regional programs (pilot and regular), aimed at the complex development of power industry on the basis of new approaches, technologies and the practician, and also the hi-tech companies of small and medium business providing development.